Pengembangan Model Empiris Penentuan Kebutuhan Air Irigasi Penyiapan Lahan Padi Sawah Hemat Air - Arif, Chusnul; Purwanto, Moh Yanuar J; Saptomo, Satyanto Krido; Sutoyo; Heryansyah, Arien; Sofiyuddin, Hanhan A. (Jurnal Teknik Sumber Daya Air, 2024)
Currently, in KP-01 the determination of irrigation water requirements for land preparation (KAIPL) for rice fields is still based on the Van de Goor & Zijlstra (VGZ) equation with the assumption of constant discharge. This method is practical in planning but tends to be wasteful in implementation. Therefore, the aim of this paper is to develop an empirical model for determining KAIPL that is more water efficient by implementing intermittent irrigation. The model was developed from the application of inundation at certain periods and water levels for three different soil textures. The empirical model was developed from the VGZ equation by adding constants as factors for intermittent irrigation and soil texture (called the MVGZ model). Then compared with the results of measurements in the field during 2 growing seasons in DI Cihea, West Java. The results show that the constant values for the MVGZ model with heavy, medium and light soil textures are 0.79; 0.76 and 0.73. With this constant, accuracy is obtained with a coefficient of determination (R2) of 0.99. Field validation results show that the MVGZ model is close to the measurement results with water savings of 28-34% compared to the VGZ model. Therefore, the MVGZ model can be applied to determine KAIPL which is more water efficient.